Applying Social Network Analysis on Rural Manufacturing of the Savannah of Bogota. (2015) - Molano, Sandra; Polo, Andrés; López, César
Abstract: In today's global volatile business environment, manufacturing organizations strive to streamline their flexibility towards delivering on time high quality products at lower costs and prices. Along this line, rural manufacturing networks constitute loosely coupled cooperation schemes among diverse partners, whose operation and interaction may be configured and synchronized in a rapid way. In order to the often unpredictable market needs to be addressed, the advantages network come from the greater scope for expanding the inter-relationships in ways that increase the scope for generating innovation. The SNA can contribute to the improvement process by focusing on the roles and the importance of key persons within process. The reason is that an improvement should focus on both, procedures and people. Therefore, the SNA, given its flexible applications, can emerge as an important management tool in the process of collection, transportation, and processing of milk in the savannah of Bogotá. The findings help to visualize the current practices at all levels when dealing with a rural manufacturing system and identify the areas in which more attentions have to be made for a more effective process.